Isoflavones' effects on pharmacokinetic profiles of main iridoids from Gardeniae Fructus in rats - Ruirui Chang; Jialin Liu; Yusha Luo; Taohong Huang; Qiang Li; Jun Wen; Weidong Chen; Tingting Zhou (Elsevier, 2020)
Gardeniae Fructus (GF) and Semen Sojae Praeparatum (SSP) are both medicine food homologies and widely used in Chinese clinical prescriptions together. The research investigated the pharmacokinetics of four iridoids in normal rats and isolfavones-fed rats, which were administered with isolfavones from SSP for 7, 14, 21 and 28 consecutive days. A validated LC-MS/MS method was developed for determining shanzhiside, genipin-1-gentiobioside, geniposide and their metabolite genipin in rat plasma. Plasma samples were pretreated by solid-phase extraction using paeoniflorin as the internal standard. The chromatographic separation was performed on a Waters Atlantis T3 (4.6 mm × 150 mm, 3 μm) column using a gradient mobile phase consisting of acetonitril and water (containing 0.06% acetic acid). The mass detection was under the multiple reaction monitoring (MRM) mode via polarity switching between negative and positive ionization modes. The calibration curves exhibited good linearity (r > 0.997) for all components. The lower limit of quantitation was in the range of 1-10 ng/mL. The intra-day and inter-day precisions (RSD) at three different levels were both less than 12.2% and the accuracies (RE) ranged from −10.1% to 16.4%. The extraction recovery of them ranged from 53.8% to 99.7%. Pharmacokinetic results indicated the bioavailability of three iridoid glycosides and the metabolite, genipin in normal rats was higher than that in rats exposed to isoflavones. With the longer time of administration of isoflavones, plasma concentrations of iridoids decreased, while genipin sulfate, the phase Ⅱ metabolite of genposide and genipin-1-gentiobioside, appeared the rising exposure. The pharmacokinetic profiles of main iridoids from GF were altered by isoflavones.